Characteristics inhibition defects of children with developmental dyscalculia: Evidence from the ERP - Chao, Wang; Wang, Enguo; Yuan, Tian; He, Qingqing; Zhang, Entao; Zhao, Junfeng (Frontiers in Psychiatry, 2022)
Developmental dyscalculia is a learning disability, especially with mathematics learning ability or lack of relevant skills and lead to mathematics achievement significantly lag behind peers. The lack of digital processing ability in children with developmental dyscalculia may be an obvious symptom of deep cognitive processing defects. In this study, we used event-related potential technology to explore the negative priming effects in children with developmental dyscalculia and in a group of healthy children. Behavioral data indicated that the variation trend of average response time of both groups was consistent under priming and controlled conditions. Developmental dyscalculia and the control group showed a significant negative priming effect. However, the magnitude of the negative priming effect was significantly different between the two groups, with the magnitude being significantly higher in the control group than that in the developmental dyscalculia group. For the ERP main components, P100, P200 and P300 amplitudes of the control group in some electrodes were significantly larger than that of the dyscalculia group. At the same time, the dyscalculia group N100 and P300 latency were significantly delayed in some electrodes than the control group. These results indicated that there were characteristics inhibition defects in children with developmental dyscalculia. Inhibition defects might be the underlying cause of the development of digital processing ability of children with developmental dyscalculia.